A Combined Technology to Protect the Anatomic Integrity of Distal Urethral Sphincter Complex in Radical Prostatectomy Improves Early Urinary Continence Recovery Without Sacrifice of Oncological Outcomes - Liu, Ao; Gao, Yi; Huang, Hai; Yang, Xiaoqun; Lin, Wenhao; Chen, Lu; Xu, Danfeng (Frontiers in Oncology, 2021)
Purpose: Our primary aim was to present a combined technique to protect the anatomic integrity of distal urethral sphincter complex (DUSC) during radical prostatectomy (RP) and discuss its impact on urinary continence (UC). The second aim was to define the learning curve. Methods: We conducted a non-randomized retrospective study. There were 314 consecutive patients who received RP by the same urologist surgeon in Shanghai Ruijin Hospital between March 2017 and April 2020. Included in this study were 263 patients with clinical T1-T2 stage. We modified a combined RP (Comb-RP) technique including endopelvic fascia no-incising technique, dorsal venous complex (DVC) no-ligation technique, intrafascial dissection technique, and anterior reconstruction technique so as to preserve the anatomic integrity of DUSC. The patients were assigned to two groups: a Comb-RP group and a conventional RP (Conv-RP) group. Continence rates were assessed every 3 months after removal of the catheter. UC was defined as 0 pads per day. Patient’s peri-operative variables including operation time, estimated blood lost (EBL), positive surgical margin (PSM), and postoperative complications were also collected. Scatter-graphs of learning curves were drawn using locally weighted scatterplot smoothing (LOWESS). Results: RP was accomplished smoothly in all 263 cases. The pad-free UC rates in Conv-RP group and Comb-RP group were 17.3% vs. 27.8% (P=0.048) at the removal of the catheter, 35.8% vs. 50.0% (P=0.027) at 1 month, 60.5% vs. 76.1% (P=0.012) at 3 months, 87.7% vs. 96.5% (P=0.022) at 6 months, and 94.7% vs. 97.7% (P=0.343) at 12 months. Kaplan-Meier analysis showed significantly higher and faster continence recovery in the Comb-RP group (mean 4.9 vs. 2.6 months, Log Rank P=0.001). There was no significant difference in PSM rate between the Comb-RP and Conv-RP group (31.1% vs. 31.2%, P =0.986). The learning curves of peri-operative variables, oncological and functional outcomes achieved the lowest point or plateau at the 20th ~60th case. Conclusions: The anatomic integrity and intact pelvic floor interplay of DUSC are important for its function. Our combined technique was a safe and feasible technique for improving early UC in RP with no significantly increased PSM rate and no significant difference in long-term UC.